Study of maternal and perinatal outcome in case of premature rupture of membrane at term - Rangrej, Ridhdhi B.; Shah, Akshay C.; Patel, Babulal S.; Parikh, Purvi M.; Patel, Kiran M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Premature rupture of membranes is characterized by the rupture of membranes before the onset of true labour. PROM is associated with a high risk of maternal morbidity and also perinatal morbidity and mortality. The objective of this study was the evaluation of various risk factors and maternal and perinatal outcomes for a better understanding of this oracular condition for its better understanding and timely management. Methods: This study was carried out on 75 cases of PROM fulfilling set criteria over one year at a tertiary care hospital of western India. Demographic details, risk factors and outcomes were studied. Results: Present study found the highest number of cases among the age group 21-24 years. 70% of patients were primigravida and almost 75% were un-booked. Around 2/3rd of cases were delivered vaginally, having the highest no of maternal and perinatal morbidity and mortality when the duration of PROM increased to more than 24 hours. Conclusions: In our study, it was seen that PROM is more commonly seen in younger primigravida having certain risk factors. Many delivered vaginally. Complications increased with increasing duration of PROM. Early recognition of premature rupture of membranes and their associated complications and appropriate management of the situation helps in reducing the problems due to PROM to a great extent.